Sebaran Particulate Matter (PM10, PM2,5, PM1, PM0,1) di SMP Negeri 1 Kota Jambi Menggunakan Model CFD (Computational Fluid Dynamics) - Febri Juita Anggraini; Annisa Shalsabila; Zuli Rodhiyah (Yayasan Literasi Sains Indonesia, 2023)
One source that contributes greatly to urban air quality is traffic. The proximity of schools to vehicles will put students at greater risk of exposure to high concentrations of particulate matter. SMP Negeri 1 Jambi City is an education center located in an urban area and adjacent to a busy road. CFD models are good at modeling the movement of pollutants in urban areas by taking into account the influence of buildings. The purpose of this study is to determine the concentration of PM10, PM2.5, PM1, and PM0.1 at SMPN 1 Jambi City based on direct measurement results and CFD modeling results and then see how accurate the modeled PM concentrations are when compared to the results of direct measurements. The results showed that the average concentrations of PM10, PM2.5, PM1, and PM0.1 from direct measurements were 20.66 µg/m3, 11.79 µg/m3, 8.74 µg/m3, and 1.96 µg/m3, respectively, while the modeling results showed lower average concentrations. The ratio of the difference between the measured and modeled PM concentrations is in the range of 11.67 - 233.45% and with the percentage of RMSPE obtained >30% (invalid), where the requirement for a modeling to be valid so that the results can be trusted in explaining the actual phenomenon is when the validity percentage is <30%.